AN ANALYSIS OF HATE SPEECH OF INDONESIAN CITIZEN COMMENTARY ON DEDDY CORBUZIER PODCAST - Monica Chesilya Sinaga; Erika Sinambela; Jubil Ezer Sihite (Jurnal Scientia, 2022)
This study aims to analyzed the types of Impoliteness strategies of hate speech in Indonesian citizen commentary on Deddy Corbuzier podcast. This study also aims to determine the dominant type of Impoliteness strategies of hate speech in Indonesian citizen commentary. This study used the theory of Culpeper’s (1996) theory on analyzed impoliteness strategies of hate speech. This study used a qualitative descriptive approach as the method of this study. The data of this study were from words, sentences and clauses in the commentary podcast. The research data consist of 100 of Indonesian citizen commentary. The findings of this study were shows that only four types of impoliteness strategies found namely Bald on Record Impoliteness, Positive Impoliteness, Negative Impoliteness and Sarcasm or Mocking Politeness. Withhold Politeness was not found on this study. The result shows that there are around 19% of Bald on Record Impoliteness were found, 35% of Positive Impoliteness, 26% of Negative Impoliteness and 20% of Sarcasm or Mocking Politeness were found in Indonesian citizen commentary. The most dominant type of impoliteness strategies was Positive Impoliteness. The most dominant type of impoliteeness strategies of hate speech were used because Indonesian Citizen on Deddy Corbuzier podcast were dominantly used to call one’s names.